Acute interstitial nephritis associated with gentamicin and lincomycin therapy. Issue 656 (June 1980) - Bell, G. M.; Thomson, D.
Abstract : A case of acute oliguric renal failure following gentamicin and linocomycin therapy is described. Renal biopsy showed an acute interstitial nephritis. This was associated with high serum gentamicin levels and the later development of ototoxicity. Withdrawal of antibiotics and conservative measures was followed by rapid recovery of renal function. Attention is drawn to the association between gentamicin and lincomycin therapy and the development of an acute interstitial nephritis.